Experimental observation of quantum mechanical fluorine tunnelling - Carsten Müller; Frederik Bader; Frenio A. Redeker; Lawrence Conrad; Helmut Beckers; Beate Paulus; Sebastian Riedel; Jean Christophe Tremblay (Nature Communications)
Abstract Quantum mechanical tunnelling occurs when a molecule transforms between two states separated by a finite energy barrier that cannot be overcome thermally. To date, it has been observed for elements up to oxygen. Efforts to go one element further are hindered by the strong bonds formed by fluorine with other elements, which suppress tunnelling. In this work, laser ablation is used to create fluorine-only species and trap weakly-bound polyfluorides in a neon matrix at cryogenic temperatures. Spectroscopic investigations reveal a temperature-dependent doublet-splitting, providing experimental evidence for heavy-atom quantum mechanical tunnelling. Theoretical modelling attributes the signal to tunnelling of the central fluorine atom in a quasi-linear [F2 ⋯  F ⋯  F2]− complex through a rotational barrier caused by steric hindrance and electronic effects in the neon matrix. The present study offers new insights into chemical interactions in polyfluorides and, more generally, of quantum phenomena in confined environments.